2017
DOI: 10.22137/ijst.2017.v2n2.04
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value and Anthelmintic Properties of Selected Leguminous Shrubs and Trees for Goats

Abstract: Two related studies were conducted to determine the nutritive value and anthelmintic properties of eight tree legumes used as goat feeds. The degradation characteristics, total extractable phenol (TPEH) and condensed tannin (CT) of Acacia (Samanea saman), Desmanthus (Desmanthus virgatus), Rensonii (Desmodium cineria), Leucaena (Leucaena leucocephala), Flemingia (Flemingia macrophylla), Gliricidia (Gliricidia sepium), Grandiflora (Sesbania grandiflora), and Sesban (Sesbania sesban) were determined.Except for Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Indigofera and Sesbania always have a higher dry matter loss than other legumes at each incubation time. The same results were also reported by Balgees et al (2013), Rahmat et al (2021), andOrden et al (2017), which showed that Indigofera and Sesbania had a higher dry matter disappearance compared to other types of tropical legumes.…”
Section: Rumen Dry Matter Degradation Of Tropical Tree Legume Leaves ...supporting
confidence: 86%
See 1 more Smart Citation
“…Indigofera and Sesbania always have a higher dry matter loss than other legumes at each incubation time. The same results were also reported by Balgees et al (2013), Rahmat et al (2021), andOrden et al (2017), which showed that Indigofera and Sesbania had a higher dry matter disappearance compared to other types of tropical legumes.…”
Section: Rumen Dry Matter Degradation Of Tropical Tree Legume Leaves ...supporting
confidence: 86%
“…According to Belachew et al (2013), one of the factors affecting insoluble fraction from DM in forage is the presence of secondary metabolites of plants, namely condensed tannin (CT). It was further reported by González et al (2002), Gupta et al (2011), andOrden et al (2017) that the CT content in plant leaves caused a decrease in leaf degradation and the increased value of insoluble fraction from the plant leaves.…”
Section: In Sacco Degradation Characteristics and Effective Degradati...mentioning
confidence: 75%